Two new species of cheilostomate Bryozoa from Iberian waters - Reverter-Gil, Oscar; Souto, Javier (European Journal of Taxonomy, 2021)
Two new species of cheilostomate bryozoans are described from material preserved in museums: Cradoscrupocellaria severoi sp. nov., from Iberian Mediterranean waters, and Setosella margaritae sp. nov., from shallow waters along the Atlantic coast of Europe. Moreover, the Mediterranean species Setosella cyclopensis Rosso, Di Martino & Gerovasileiou, 2020 is reported in Iberian waters for the first time.